Effect of laser shock processing with post-machining and deep cryogenic treatment on fatigue life of GH4169 super alloy. (February 2019) - Sun, Jianfei; Su, Anpeng; Wang, Tianming; Chen, Wuyi; Guo, Wei
Highlights: A hybrid manufacturing method called laser shock processing with post-machining (LSPM) was proposed. Suitable machining parameters superposed laser shock processing can affect distribution of residual stress. LSPM may significantly improve fatigue life of a machined component. Grain grew significantly after deep cryogenic treatment, thus made a reduction of fatigue life. The variation of fatigue striations width reflected the fatigue resistance. Abstract: To achieve better fatigue behavior for super alloy GH4169 parts, residual compressive stresses in surface layers were expected by machining or other manufacturing method. Both laser shock processing (LSP) and deep cryogenic treatment (DCT) were thought as residual stress improvement methods, but their influences on fatigue life were still inexplicit and need further investigation. Four groups of standard specimens are manufactured to study their residual stresses distribution and micro structure of their surfaces on fatigue behavior. To avoid LSP's disadvantage in application, a hybrid manufacturing method of laser shock processing with post-machining (LSPM) was proposed. Results shows that fatigue life for specimens increased more than twofold after LSPM, whereas DCT brought reductions in fatigue life.